Emprego de geotecnologias no diagnóstico de produção e espacialização das agroindústrias familiares no município de Francisco Beltrão, PR - Grabaski, Christine Nascimento (2008)
The family agro industries constitute an alternative that generate income around the country. The products manufactured must follow the sanitary legislation viewing the alimentary and nutritional security of the consumers. The regularization and inspection are due to the counties, state and federal government since the decentralization promoted by the Brazilian Federal Constitution of 1998. By the application of geotechnologies, the specialized register of family agro industries allows the inspection of events as agglomerations and concentrations of activities in a determined territorial space. Twenty nine agro industries of animal origin products work in Francisco Beltrão, South west of Paraná. They process milk, pork meat, chicken, eggs, honey and fish. Through the application of different methodologies, involving the collection of geographic coordination using a GPS GARMIN 12 XL device following the transference of theses points to image letter of satellite LANDSAT 7 was manufactured cartograms by activity groups. Using a relational databank from the Campeiro Software 6.0® by the geometic lab of UFSM, the quantitative analysis of production were accomplished. At the fourteen milky industries, the work force applied was the family one. Contracted workforce in 7% of the units. At the eith slaughtering pork meat industries, the family work force is the same of the contracted workforce, with an index of 2,75 family unit /man per industries. The fish slaughtering are concentrated between the coordinate 26º00 to 26º08 S of latitude and 53º10 O of longitude, next the urban area. The results showed the generation of work and income at the agro industries with SIM, sustainability of the processes used, an improvement of farmers quality life revealed by the grade of satisfaction pointed by the workers involved family work production. The average degree was between 7,5 to 8,0 (in a scale of 0 to 10). The consolidation of these local brands is determining factor for the success of the business. The results will help to manufacture local and sustainable projects/plans of development.